Design, Synthesis, and Antitumor Activity of Erlotinib Derivatives - Long-fei Mao; Zhen-Zhen Wang; Qiong Wu; Xiaojie Chen; Jian-Xue Yang; Jian-Xue Yang; Xin Wang; Yue-Ming Li (Frontiers in Pharmacology, 2022)
Nineteen erlotinib derivatives bearing different 1,2,3-triazole moieties were designed, synthesized, and evaluated for their potential against different cancer cell lines. The structures of the synthesized compounds were confirmed via1H NMR, 13C NMR, and HR MS. Preliminary antitumor activity assay results suggested that some compounds showed remarkable inhibitory activity against different cancer cell lines including the corresponding drug-resistant ones. Among these compounds, 3d was the most promising one with an IC50 of 7.17 ± 0.73 μM (KYSE70TR), 7.91 ± 0.61 μM (KYSE410TR), 10.02 ± 0.75 μM (KYSE450TR), 5.76 ± 0.3 3 μM (H1650TR), and 2.38 ± 0.17 μM (HCC827GR). A preliminary mechanism study suggested that compound 3d suppressed cancer cell proliferation through the EGFR-TK pathway.